Increased sexual dimorphism in dense populations of Olive-backed Sunbirds on small islands: morphological niche contraction in females but not males. (3rd July 2019) - O'Connell, Darren P.; Kelly, David J.; Kelly, Seán B. A.; Sealy, Síofra; Karya, Adi; Analuddin, Kangkuso; Marples, Nicola M.
ABSTRACT: Competition takes place not only between species but also within them. Intersexual competition for resources may increase sexual dimorphism in body size to minimise ecological niche overlap. Change in the level of sexual dimorphism in a species is a common feature of island radiations. This is often interpreted as ecological release from interspecific competitors absent from small islands, allowing niche expansion by both sexes of a dimorphic species. The Olive-backed Sunbird ( Cinnyris jugularis ) is a widespread island-colonising species found throughout the Indo-West Pacific. Here we investigate sexual dimorphism in morphological niche of Olive-backed Sunbird populations in South-east Sulawesi, Indonesia. We found decreased overlap in morphological niche between females and males on the species-depauperate Wakatobi Islands, in comparison to mainland Sulawesi and its larger continental islands, indicating greater sexual dimorphism on the small islands. This change in sexual dimorphism was associated with a decrease in the morphological niche hypervolume of females, but no change in males. Therefore there was no indication of expansion of morphological niche space in the absence of mainland competitors. These morphological differences were associated with the significantly higher population density of Wakatobi Olive-backed Sunbirds. Therefore this increased sexual dimorphism may serve to alleviate intraspecific competition for resources.